Pengujian Sistem pada Website Linkundangan dengan Metode Alpha dan Beta Testing - Ghazi Alghifari Sudrajat; Iqbal Hafidz Ramadhan; Muhammad Rakha Nur Rizqi; Rama Trihandika Malau; Zacky Aulia Hafizh; Zaki Mubarok (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2026)
This study aims to test the functionality and user satisfaction level of the LinkUndangan web-based application using the Black Box Testing method consisting of Alpha Testing and Beta Testing. LinkUndangan is an online digital invitation creation and management platform. Alpha Testing was conducted by the internal team to ensure all main functions such as user login, account registration, invitation creation, photo upload, preview, publication, and RSVP run according to functional specifications. Meanwhile, Beta Testing involved 30 end-user respondents using a Likert scale questionnaire instrument based on ISO 9241-11:2018 usability standards and ISO/IEC 25010:2023 quality models. The Alpha Testing results showed a 100% success rate across 7 test scenarios with no critical functional errors found. The Beta Testing results achieved an average user satisfaction score of 71.67%, categorizing it as good, with Functional Correctness reaching 76.00% and Functional Suitability at 75.33%. These results conclude that the LinkUndangan website is fit for deployment as a web-based digital invitation platform.